Five star music makeover : the independent artist's guide for singers, songwriters, bands, producers, and self-publishers. - Sheehan, Coreen; Paris, Anika; Corne, Eric, 1970-; Eames, Michael, 1967-; Borg, Bobby (MusicPro guides., 2016)
In order to achieve success in today's music industry, artists must first do a great deal of work on their own. Learning the required skills can take years of real-life experience, and hiring personal coaches, studio professionals, and consultants can be costly. But now, for the first time, there's an invaluable resource to help you meet these challenges. Five Star Music Makeover is an engaging all-in-one guide designed specifically for aspiring artists. Written by five experts with over 100 years of collective experience, both on and off the stage, this unique book covers five key skills every musician needs to succeed: (1) improving vocal production/technique; (2) writing memorable and marketable songs; (3) recording your ultimate EP; (4) navigating the publishing world; and (5) promoting music effectively. Also included are insiders' stories and anecdotes, helpful tips, creative exercises, celebrity interviews, and all the practical expertise necessary to develop a successful music career. Five Star Music Makeover is a complete and practical career guide, a resource that transforms artists from good to great.